Effect of Skin Protection and Skin Irritation on the Internal Exposure to Carbon Disulfide in Employees of the Viscose Industry - Kilo, Sonja; Zonnur, Nina; Uter, Wolfgang; Göen, Thomas; Drexler, Hans (Annals of Occupational Hygiene, 2015)
Occupational exposure to carbon disulfide (CS2) leads to inhalative and dermal uptake and thereby to internal exposure. In order to prevent occupational contact dermatitis, gloves and skin protection creams are used at the workplace. The aim of the study was the evaluation of the influence of personal skin protection and irritation on the internal exposure to CS2 of employees in the viscose industry.One hundred and eighty-two male CS2-exposed employees were included in the study and were examined regarding working conditions, use of personal protective measures und skin status. Personal air monitoring and biological monitoring was performed and the 'relative internal exposure' (RIE, internal exposure in relation to external exposure) calculated. A multiple regression analysis calculated the influence of skin protection and irritation on CS2 uptake.Usage of skin protection creams and gloves (and both in combination) while working was associated with a significantly higher RIE indicating a higher dermal penetration of CS2. Equally, irritated skin and younger age was associated with a higher internal burden.Gloves and skin protection creams are useful for preventing occupational skin diseases. However, when handling skin-resorptive substances like CS2, they can increase internal exposure or skin irritation. Therefore, we recommend the careful consideration of benefits and risks of protective creams and gloves at the workplace.
EVALuna2:5491